ANALISIS PERAN MASJID SEBAGAI PUSAT PEMBERDAYAAN EKONOMI UMAT (Studi Kasus Masjid Agung Jami’ Kota Malang) - Al Huda, Panglima Thariq (Jurnal Ilmiah Mahasiswa FEB, 2017)
Mosque is one of the aspects cannot be separated from the Islam either cultural, spiritual and social of muslims. One of them is economic society empowerment. The majority Malang’s people are muslims where one of Malang’s landmark is Agung Jami’ Kota Malang Mosque. The mosque holds the only one agung in Malang City. One of the mosque activity is doing economic society empowerment. The purpose of this study are to know the role of Agung Jami’ Kota Malang Mosque to economic society empowerment through infaq and sadaqah. The approach used in this research  is descriptive  qualitative.  Based  on  the results,  showed  gung  Jami’  Kota  Malang Mosque just to distribute infaq and sadaqah according to its purpose.Keywords: Empowerment, Empowerment Based Mosque, Infaq and Sadaqah, Islamic Economics.